Day 2 Thu, February 16, 2017 2017
DOI: 10.2118/185017-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Polymer Flooding with Crossflow in Layered Reservoirs Considering Viscous Fingering

Abstract: Polymer flooding has been commercially applied to a number of viscous oil fields in the past decade and gradually gained more popularity. Due to limited injectivity in viscous-oil reservoirs, a relatively low polymer viscosity is usually used to avoid excessive injection pressure. In such a case, mobility ratio of polymer solution to oil is much greater than one, which implies unstable flow and strong viscous fingering. Existing reservoir simulators lack the capability of modeling such a physical phenomenon. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While the other authors considered adsorption as a potential retarding process, dispersion has different effects which are harder to account for. This work shows clearly the effect of interaction of factors that affect fluid movement, such as heterogeneity, fluid mobility, retardation effects that induced by adsorption, desorption, dispersion and diffusion hence predicting sweeping performance and invaded zone in each layer, where the need of such work is observed (Lake et al 2014;Luo et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…While the other authors considered adsorption as a potential retarding process, dispersion has different effects which are harder to account for. This work shows clearly the effect of interaction of factors that affect fluid movement, such as heterogeneity, fluid mobility, retardation effects that induced by adsorption, desorption, dispersion and diffusion hence predicting sweeping performance and invaded zone in each layer, where the need of such work is observed (Lake et al 2014;Luo et al 2017).…”
Section: Discussionmentioning
confidence: 94%
“…q(t) is the injection rate, m 3 /s; k is the absolute permeability,10 −3 µm 2 ; h is the net pay thickness, m; f w is the second derivative of the water-oil fractional flow curve, dimensionless; µ w is the water viscosity, mPa•s; µ o is the oil viscosity, mPa•s; k rw is the water-phase relative permeability, dimensionless; k rw is the oil-phase relative permeability, dimensionless; S wf is the frontal saturation of the oil-water two-phase flow region, dimensionless; S wm is the maximum water saturation at the injection well bottom, dimensionless; S wc is the irreducible water saturation, dimensionless; r w is the bottom hole radius, m; r w 1 is the distance between the injection well bottom and the water zone front, m; r w 2 is the distance between the injection well bottom and the water-oil two-phase zone front, m; r d is the distance between the injector and producer, m; and m is the ratio of producers to injectors in the well pattern. By combining Equations (22), (23), (24), and (25), the total pressure difference between injector and producer before water breakthrough is:…”
Section: Pressure Difference Between Injector and Producer In Water Fmentioning
confidence: 99%
“…He also pointed out that in a layered reservoir, injecting polymer solutions enforced cross flow between layers with different properties, which accelerated the oil displacement in low-permeability layers. Luo [24] developed an implicit well-rate allocation model to accurately allocate the injection rate into different layers with contrasting permeabilities. Lu [25] defined several flow regions with unique saturation profiles during polymer flooding, and then established a semi-analytical model for predicting multilayer injection capacity.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, several studies have overcome this issue by implementing new mathematical models to scale up and consider the influence of VF. For example, Luo et al [ 25 27 ] implemented the Effective Fingering Model, capable of considering VF effects in heavy oil displacements driven by water flooding and polymer flooding. The model developed by Luo et al showed that these simulators could consider the effects of VF, having quantitative fair agreement compared to experimental and field data.…”
Section: Introductionmentioning
confidence: 99%